ETNOGRAFI KOMUNIKASI TRADISI AYUN BUDAK PADA ADAT MELAYU SIAK DI KOTA DUMAI PROVINSI RIAU - Neno Lestari; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The Ayun Budak tradition in Dumai City is part of the culture which inherited hereditary from the Siak Malay’s custom. Technically, the tradition done by the parents to calm their crying child or make it as a lullaby. However, the Ayun Budak is important for the locals in case of consisting the local wisdom such as forming character, an expression of hapiness and grateful to Allah subhanawata’ala, as a media to offered advices, also to strengthen the relations among the locals. So that the tradition established as the succession of custom which held simultaneously or not with aqiqah. The aim of this research is to ascertain how the communication activity in Ayun Budak which setted as one event called Ayun Budak ceremonial.The method that used in this research is qualitative method with etnography communication approach. The datas gathered through observation, interview and documentation. There are 10 (ten) informant that determined by purposive sampling technique.The result of this research shows that the communicative situasion in Ayun Budak ceremonial could be done in parent’s home, the males seat in the front room and females in the back room of the house. The communicative occasion based in the type of the occasion that is opening and the verse to be sung. The discourse topic is an expression of gratefulness to Allah subhanawata’ala, offering advice and praying. Purpose and function of this tradition as an instrument to strengthen the relations, trancendental feelings, and gratefulness. The setting of Ayun Budak is in parents home and unbound to the time which attended by theologians, traditional leader, tambourine group, and elders whether from the inner family or local communities. The message shaped verbally and nonverbally. It consists advice, religious advice, and character forming. The step of the event does not begin by opening, marhaban and barzanji and the child is to be swung. Interaction theorem is rule and norm which exist in the event, interpretation norm in Ayun Budak drives to courtesy, sociability or kindness, and respecting each other, also obey and understand to religion and custom principles. Whereas in communicative acts mean people who understand the Ayun Budak are tradition leader, theologians, tambourine group, and the elders.Keyword: Tradition, Ayun Budak Tradition, Ethnography Communication